The effect of adding borax on the Oxy-Acetylene Welding (OAW) process on tensile strength of ST42 steel - Moh. Jufri; Hendaryati, Heni; Nur Subeki; Pramojo, Mita Putri Bambang; Baiq Firyal Salsabila Safitri (University of Muhammadiyah Malang, 2024)
The welding process aims at joining materials, especially metals or thermoplastic for certain purposes. It melts the materials in the joining process. In some cases, such material is difficult to be joined with the welding process. Therefore, an appropriate flux is needed in this process. The effect of adding borax in the welding process of OAW is the focus of this research. The research was conducted using the experimental method of adding 1 gram, 3 grams, and 5 grams of borax to the brass and ST42 steel welding process. Borax was added to aid the adhesion process between brass and steel as both have different properties. This research results in the highest elongation value in 1 gram of borax addition; the elongation is 3.9935 cm. Meanwhile, adding 1 gram of borax also affects the welding joints’ ultimate tensile strength (UTS). It results in the highest UTS value of 9.961779 kN/mm2 among the other weight variations of borax addition. It indicates that the borax addition with proper weight in the welding process affects the joints. Moreover, the borax addition in the welding process influences the elongation values, ultimate tensile strength, and modulus of elasticity of the welding joints.